2005
DOI: 10.1097/01.jnen.0000190067.20935.42
|View full text |Cite
|
Sign up to set email alerts
|

Grey Matter Pathology in Multiple Sclerosis

Abstract: The aim of our study is to evaluate the extent and distribution of grey matter demyelinating lesions in multiple sclerosis (MS), addressing also neuronal loss and synaptic loss. Whole coronal sections of 6 MS brains and 6 control brains were selected. Immunohistochemistry was performed for myelin basic protein, neurofilaments, synaptophysin, ubiquitin, and activated caspase-3. Neuronal density and optical density of synaptophysin staining were estimated in cortical lesions and compared with those observed in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
220
3
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(245 citation statements)
references
References 39 publications
16
220
3
6
Order By: Relevance
“…The level of IL-9 is significantly increased in patients with atopic myelitis; however, this value was not elevated in our patient (17,18). Although MS is regarded to be a white matter disease, recent histopathological studies of early MS (25)(26)(27)(28)(29) have revealed lesions in the leptomeninges and gray matter to be important initial targets of the MS process. Furthermore, re-cent studies have extended the earlier concept of MS, namely that the inflammation observed in MS is principally mediated by CD4+ type I helper T-cells.…”
Section: Discussionmentioning
confidence: 47%
“…The level of IL-9 is significantly increased in patients with atopic myelitis; however, this value was not elevated in our patient (17,18). Although MS is regarded to be a white matter disease, recent histopathological studies of early MS (25)(26)(27)(28)(29) have revealed lesions in the leptomeninges and gray matter to be important initial targets of the MS process. Furthermore, re-cent studies have extended the earlier concept of MS, namely that the inflammation observed in MS is principally mediated by CD4+ type I helper T-cells.…”
Section: Discussionmentioning
confidence: 47%
“…If cortical atrophy is the result of axonal transection by WM lesions, then highly connected regions should be more vulnerable than regions with relatively fewer connections. However, it is also possible that these gray matter regions are somehow intrinsically more vulnerable to direct involvement by the disease; indeed, histopathological studies have demonstrated that the cingulate gyrus, temporal lobe, and insula generally show a higher prevalence of cortical demyelinated lesions than other areas (Bö et al, 2003;Vercellino et al, 2005;Kutzelnigg and Lassmann, 2006). Two studies on relatively small numbers (n = 30 and 26) of MS patients reported a correlation between fractional GM volume and total WM lesion volume, but not disability (Ge et al, 2001;Chard et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This seems low, but the coronal sections were sampled from more frontal regions of the brain, a preferential area for cortical pathology, 22,23 but not far for WMLs, which are more frequently located periventricular.…”
Section: Discussionmentioning
confidence: 99%